2014
DOI: 10.21608/ajesa.2014.4901
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Influence on Development and Life Table Parameters of the Acarid Mite, Caloglyphus manuri Eraky & Osman Reared on the Root-Knot Nematode, Meloidogyne sp.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Generally, male immatures had shorter life cycle than these of female. Similar results were obtained by Abou El-Atta et al (2014) who mentioned that the life cycle of C. manure durated 7.42 days for female and tall days for male days at 30°C; Eraky (1987) when reared C. berlesei (Mich.) on yeasted Dorosophila, the life cycle lasted 7.5 days at 26°C; Woodring (1969) stated that life cycle of Caloglyphus anomalus averaged 6.5 days at 23°C; whereas, Walia and Mathur (1998) indicated that Tyrophagous putrescentiae (Schrank) female life cycle durated 13.12 days when reared on juvenile of root the knot nematode (Meloidogyne javanica). Chmielewski (2000) reported that female C. berlesei life cycle was 19.90 days when fed on bee-bread, while in ( 2003) he found that its life cycle decreased to 17.7 days when reared on buck wheat sprouts at 20°C and 95-100% R.H. Also, Eraky and Osman (2008 b) reported that female and male C. manuri (Mich.) life cycle durated 10.40 and 8.10 days, respectively when reared on Meloidogyne sp.…”
Section: Life Cyclesupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, male immatures had shorter life cycle than these of female. Similar results were obtained by Abou El-Atta et al (2014) who mentioned that the life cycle of C. manure durated 7.42 days for female and tall days for male days at 30°C; Eraky (1987) when reared C. berlesei (Mich.) on yeasted Dorosophila, the life cycle lasted 7.5 days at 26°C; Woodring (1969) stated that life cycle of Caloglyphus anomalus averaged 6.5 days at 23°C; whereas, Walia and Mathur (1998) indicated that Tyrophagous putrescentiae (Schrank) female life cycle durated 13.12 days when reared on juvenile of root the knot nematode (Meloidogyne javanica). Chmielewski (2000) reported that female C. berlesei life cycle was 19.90 days when fed on bee-bread, while in ( 2003) he found that its life cycle decreased to 17.7 days when reared on buck wheat sprouts at 20°C and 95-100% R.H. Also, Eraky and Osman (2008 b) reported that female and male C. manuri (Mich.) life cycle durated 10.40 and 8.10 days, respectively when reared on Meloidogyne sp.…”
Section: Life Cyclesupporting
confidence: 91%
“…These results illustrated that males lived longer than female. Similar data obtained by Abou El-Atta et al (2014) who stated that the adult female lived for 27.20, 20.55 and 16.95 days while male lived for 16. 85, 18.40 and 9.30 days20, 25 and 30°C, respectively.…”
Section: Adult Longevitysupporting
confidence: 87%